Super (a, d)-hyperedge antimagic total labeling on hypergraphs of the volcano graph, semi parachute graph, and comb product graph - Adawiyah, Robiatul; Asari, Okta Endri; Dafik, Dafik; Kristiana, Arika Indah; Prihandini, Rafiantika Megahnia; Rohini, A (Fakultas Tarbiyah Universitas Ibrahimy, 2025)
In graph theory, understanding the labeling of graphs and hypergraphs provides valuable insights into their structural properties and applications. A hypergraph generalizes the notion of a conventional graph, defined as a mathematical structure built from a vertex set V and a hyperedge set E, where each hyperedge is allowed to connect two or more vertices simultaneously. The essential distinction between a graph and a hypergraph lies in their edges. While in a graph a single edge connects exactly two vertices, in a hypergraph a single hyperedge may connect any number of vertices, including two. A hypergraph is considered to admit a super (a, d) -hyperedge antimagic total labeling, such that the vertex label functions f: V(H)  1, 2, 3, ....., V(H) then f: E(H)  V(H) + 1, ....., V(H) + V(H) and weight w(ei) = ∑ f(ei) + ∑ f(Vi,j), where i denotes the number of hyperedges, j represents the number of vertices contained in a hyperedge, and e_i refers to the set of vertices and its associated edges with weight w(ei) for each hyperedge. A super (a, d) -hyperedge antimagic total labeling is formulated as a labeling scheme based on arithmetic progressions, where ???? serves as the initial value and d denotes the common difference between consecutive labels. In this scheme, the total weight of a hyperedge is determined by deriving from the sum of the vertex labels and the label of the respective hyperedge. The labels are arranged in an arithmetic sequence, ensuring that each hyperedge has a distinct weight. This study focuses on several special classes of hypergraphs, namely, the volcano graph, the semi-parachute graph, and the comb product of graphs, to implement and examine the characteristics of the super (a, d)-hyperedge antimagic total labeling. By focusing on these graph classes, the study contributes to combinatorics by offering a deeper understanding of hypergraph labeling schemes and their potential applications in network theory, coding theory, and data modeling.